Citizens´ services : Nordic and Baltic research needs - Albinsson, Lars (Högskolan i Borås, Institutionen Handels- och IT-högskolan, 2009)
What are the key issues in citizen-centric service development that research should address? People engaged in the development of services for citizens, both public and private, in six countries – Iceland, Sweden, Lithuania, Norway, Estonia and Latvia – have participated in half-day workshops during 2008-2009 to discuss the challenges research projects should take on, which output is needed and how to conduct them in order to better help service developers. This work has been a key part of the project “Citizens’ services – Turning Public Private outside in”.In general, the situation in the six countries is very similar and key findings include:•The need to improve cross- and inter-organizational service development. There are too many “silos”.•The need to better engage citizens in service design, to increase the use and effectiveness of services.•The need for more collaborative research projects with researchers, and public and private service developers in an action-oriented and experimental mode. Sponsorship : VINNOVA